2019
DOI: 10.1590/1678-4499.20180386
|View full text |Cite
|
Sign up to set email alerts
|

Local genotypes of dog rose from Interior Aegean region of Turkey as a unique source of pro-health compounds

Abstract: Rosehip, Rosa canina L. fruit, is valued for its flavor, taste, color and aroma, in accordance with its recognition as one of richest sources of pro-health compounds. Screening, preservation and propagation of the most valuable local populations of rosehip are performed for food, pharmacological, and cosmetic applications. Eleven native R. canina genotypes from the Interior Aegean region, Turkey, were collected and analyzed regarding organic acids, phenolic compounds, sugars, and DPPH scavenging activity withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(46 reference statements)
2
7
1
Order By: Relevance
“…Ilyasoglu (2014) reported that the antioxidant activity of methanolic extract of rosehip seeds was 10.40 μmol TE/g (260.3 mgTE/100 g) with TEAC method. Okatan et al, (2019) studied DPPH antioxidant capacity of different genotypes of rosehip fruits. They reported the average DPPH activity of rosehip fruits as 169.1 μg/ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilyasoglu (2014) reported that the antioxidant activity of methanolic extract of rosehip seeds was 10.40 μmol TE/g (260.3 mgTE/100 g) with TEAC method. Okatan et al, (2019) studied DPPH antioxidant capacity of different genotypes of rosehip fruits. They reported the average DPPH activity of rosehip fruits as 169.1 μg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Rosa canina L. (Rosehip or dog rose) belongs to the Rosaceae family, Rosa genus which has around 100 species distributing in North America, Europe, the Middle East, and Asia (Ercisli, et al, 2007). Rosehip species is resistant to environmental stress factors and can be grown at low soil fertility or a harsh climate wherever from valleys to high altitude plateaus, even above 1,500 m altitude (Okatan et al, 2019). Among all, 25 species are spread throughout Turkey (Ercisli, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies described variability in thorn and yield of Rosa ecotypes [32][33][34][35]. The fruit weight of rose hip ecotypes belonging to different species that were reported in Turkey ranged from 0.61 to 4.95 g [32,33,[35][36][37]. At the individual level, promising ecotypes were found in both R. canina and R. dumalis species.…”
Section: Morphological Traits Of R Canina and R Dumalis Ecotypesmentioning
confidence: 99%
“…It is well understanding that wild species increase crop genetic diversity [39,43]. Frequent seed propagation of wild fruits and strictly out-crossing nature probably leads to an increase in the genetic diversity of wild fruits [37][38][39] Total flavonoid, total phenolic, total carotenoid, Vitamin C, total anthocyanin, antioxidant capacity and SSC content of R. canina and R. dumalis ecotypes are shown in Table 2. Total flavonoid content was the highest in K6 (2.04 mg per g FW), which belongs to R. dumalis, followed by K3 (1.94 mg per g FW), while it was the lowest in K9 (0.88 mg per g FW) (Table 2).…”
Section: Morphological Traits Of R Canina and R Dumalis Ecotypesmentioning
confidence: 99%
See 1 more Smart Citation